1997
DOI: 10.1007/s002030050409
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory stimulation and generation of superoxide radicals in Pseudomonas aeruginosa by fungal naphthoquinones

Abstract: The mechanism of action of antimicrobial naphthoquinones from the fungus Fusarium was studied by using Pseudomonas aeruginosa. Bostricoidin, methyl ether fusarubin, and fusarubin stimulated the oxygen consumption of bacterial cells and induced cyanide-insensitive oxygen consumption. These activities of the tested compounds were also observed in bacterial membrane preparations in a dose-dependent manner. Naphthoquinones stimulated the generation of superoxide anion and hydrogen peroxide. The naphthoquinone effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
1
18
0
1
Order By: Relevance
“…Many microbial napthaquinones and aza-anthraquinones compounds exhibit antimicrobial activity with a specific mode of action [ 32 ]. These metabolites have been reported to inhibit various macromolecular syntheses by a secondary effect of the action on respiratory electron transport [ 32 , 33 ]. Bostrycoidin and fusarubin can stimulate cellular respiration and membrane NADH oxidation of bacteria, thereby, exhibit antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many microbial napthaquinones and aza-anthraquinones compounds exhibit antimicrobial activity with a specific mode of action [ 32 ]. These metabolites have been reported to inhibit various macromolecular syntheses by a secondary effect of the action on respiratory electron transport [ 32 , 33 ]. Bostrycoidin and fusarubin can stimulate cellular respiration and membrane NADH oxidation of bacteria, thereby, exhibit antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Bostrycoidin and fusarubin can stimulate cellular respiration and membrane NADH oxidation of bacteria, thereby, exhibit antimicrobial activity. Cytotoxicity of the quinones exhibited resulting from their interaction with NADH complex I and intercalation of DNA [ 2 , 33 ]. Further investigation is required to understand the mechanism of actions of the isolated napthaquinones and aza-anthraquinones groups from Fusarium solani .…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have also been reported to act as arylating electrophiles and to form irreversible complexes with nucleophilic amino acids in proteins which, in turn, could lead to their inactivation [27]. It was also shown that naphthoquinones stimulate respiratory oxidation as well as superoxide and H 2 O 2 generation in bacterial cells [28]. Many naphthoquinones (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds act as inhibitors of electron transport and uncouplers of oxidative phosphorylation and give rise to a wide range of cytostatic and antiproliferative activities [ 24 ]. 1,4-Naphthoquinones (i.e., juglone, plumbagin, and lawsone) are an interesting subgroup of quinones that displays remarkable biological properties [ 25 27 ]. The biological activity shown by 1,4-naphthoquinones relies upon their ability to accept one and/or two electrons to form radical anion or hydroquinone [ 28 ], which leads to the generation of reactive oxygen species (ROS) such as hydrogen peroxide and superoxide that cause cell damage [ 29 ].…”
Section: Introductionmentioning
confidence: 99%